Is a larger specialist nurse workforce in cancer care associated with better patient experience? Cross-sectional study. (April 2013) - Griffiths, Peter; Simon, Michael; Richardson, Alison; Corner, Jessica
Objectives: To assess whether variation in the provision of cancer specialist nurses is associated with the experiences of care for patients undergoing treatment for cancer. Methods: This is a cross-sectional study using routinely collected national survey data in 158 acute hospital National Health Service (NHS) Trusts in England. Patients with a primary diagnosis of cancer who attended hospital as inpatients or day cases in the first three months of 2010 responded to a national survey ( n = 67, 713, response rate 67%). Patient perceptions of coordination of care, quality of information provision, emotional support and support for symptom management were studied. Results: Patients in Trusts that had the fewest patients per specialist nurse were more likely to report that people treating and caring for them worked well together (adjusted odds ratio 1.08, 95% confidence interval 1.01–1.15; p = 0.02) and provided enough emotional support during ambulatory treatment (1.15, 1.01–1.32; p = 0.04), but were no more likely to report being given the right amount of information (0.96, 0.88–1.05; p = 0.38) when compared to patients in Trusts with the most patients per specialist nurse. Breast cancer patients undergoing chemotherapy in the Trusts with fewer patients per specialist nurse were more likely to report good support for the control of side effects from chemotherapy (1.34, 1.02–1.75; p = 0.03). Conclusions: Cancer patients' experience of care coordination and emotional support was better in Trusts with more specialist nurses. The absolute differences were small, and it was unclear whether particular roles or service configurations are associated with better experience.